Utility of a virtual counselor (VICKY) to collect family health histories among vulnerable patient populations: A randomized controlled trial. Issue 5 (May 2021) - Wang, Catharine; Paasche-Orlow, Michael K.; Bowen, Deborah J.; Cabral, Howard; Winter, Michael R.; Norkunas Cunningham, Tricia; Trevino-Talbot, Michelle; Toledo, Diana M.; Cortes, Dharma E.; Campion, MaryAnn; Bickmore, Timothy
Highlights: The usability of digital family history tools has important implications for the quality of the data collected. Use of a virtual counselor to collect family histories can overcome literacy-related barriers to using digital tools. Additional research is needed to understand factors (e.g., language version, stigma) that may influence accuracy outcomes. Abstract: Objectives: This study is a randomized controlled trial comparing the efficacy of a virtual counselor (VICKY) to the My Family Health Portrait (MFHP) tool for collecting family health history (FHx). Methods: A total of 279 participants were recruited from a large safety-net hospital and block randomized by health literacy to use one of the digital FHx tools, followed by a genetic counselor interview. A final sample of 273 participants were included for analyses of primary study aims pertaining to tool concordance, which assessed agreement between tool and genetic counselor. Results: Tool completion differed significantly between tools (VICKY = 97%, MFHP = 51%; p < .0001). Concordance between tool and genetic counselor was significantly greater for participants randomized to VICKY compared to MFHP for ascertaining first- and second-degree relatives (ps<.0001), and most health conditions examined. There was significant interaction by health literacy, with greater differences in concordance observed between tools among those with limited literacy. Conclusions: A virtual counselor overcomes many of the literacy-related barriers to using traditional digital tools and highlights an approach that may be important to consider when collecting health histories from vulnerable populations. Practice implications: The usability of digital health history tools will have important implications for the quality of the data collected and its downstream clinical utility.